Bridging climate science, policy, and communities: collaborative pathways for climate resilience in the Indo-Pacific - Modi, Aditi; Roxy, Mathew Koll; Jain, Shipra; Truong, Chi Huyen; Doan, Quang-Van; Jack, Christopher; Jevrejeva, Svetlana; Singh, Arvind; Dhara, Chirag; Ghosh, Sahana (Frontiers in Climate, 2025)
The Indo-Pacific region, a critical economic and geopolitical hub, faces intensifying climate risks, including accelerating sea-level rise, extreme weather events—particularly heatwaves amplified by rapid urbanization—and glacial retreat in the Hindu Kush Himalayas. While advancements in climate science have significantly improved future climate projections, gaps remain in translating this knowledge into actionable adaptation strategies. Barriers such as data inaccessibility, weak institutional and international coordination, and financial constraints hinder effective climate action. This study synthesizes existing climate knowledge for the Indo-Pacific region, emphasizing the need for localized, community-driven adaptation approaches. Key challenges include the vulnerability and exposure of coastal communities to sea-level rise, the limitations of current urban-scale climate modeling, and the underrepresentation of sociocultural factors in climate adaptation strategies. The integration of Artificial Intelligence (AI) and machine learning (ML) in climate models presents an opportunity to enhance urban climate resilience, while the incorporation of indigenous knowledge rooted in scientific principles offers a critical pathway to improving localized adaptation efforts. Additionally, science communication plays a pivotal role in ensuring that climate research reaches policymakers and communities in an accessible and actionable manner. We advocate for a paradigm shift from a linear value chain to a value cycle approach, where scientific insights inform policy and local contexts inform research priorities. By bridging climate science, policy, and communities through regional platforms such as the Indo-Pacific My Climate Risk Hub at the Indian Institute of Tropical Meteorology (IITM) Pune, India, this paper outlines pathways for collaborative climate action. This work proposes actionable strategies for regional resilience.